PENERAPAN STRATEGI STUDENT CENTERED APPROACH (SCA) DENGAN BANTUAN MEDIA YOUTUBE TERHADAP KEMAMPUAN LITERASI DAN PENALARAN MATEMATIS PESERTA DIDIK SMA - Putri, Ikko Vinesti Armelia; Anggoro, Bambang Sri; Dewi, Novian Riskiana (Program Studi Pendidikan Matematika, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Balikpapan, 2026)
This study aimed to determine the effect of the Student-Centered Approach (SCA) assisted by YouTube media on the mathematical literacy and mathematical reasoning abilities of tenth-grade students at MAN 1 Bandar Lampung. The study employed a quantitative approach using a quasi-experimental method with a post-test-only control group design. The research sample consisted of two experimental classes that received instruction through the Student-Centered Approach (SCA) assisted by YouTube media and one control class that was taught using the Discovery Learning model. Data were collected through tests measuring students' mathematical literacy and mathematical reasoning abilities and were analyzed using Multivariate Analysis of Variance (MANOVA). The results revealed that the average scores of mathematical literacy and mathematical reasoning in the experimental classes were higher than those in the control class. Hypothesis testing indicated that the Student-Centered Approach (SCA) assisted by YouTube media did not have a significant effect on students' mathematical literacy ability (sig. = 0.056 > 0.05). However, it had a significant effect on students' mathematical reasoning ability (sig. = 0.020 < 0.05). Furthermore, the MANOVA results showed that the Student-Centered Approach (SCA) assisted by YouTube media had a simultaneous effect on both mathematical literacy and mathematical reasoning abilities (sig. = 0.035 < 0.05). Based on these findings, it can be concluded that the Student-Centered Approach (SCA) assisted by YouTube media is effective in improving students' mathematical reasoning ability and has a simultaneous influence on both mathematical literacy and mathematical reasoning abilities.